The nine residue plasminogen-binding motif of the pneumococcal enolase is the major cofactor of plasmin-mediated degradation of extracellular matrix, dissolution of fibrin and transmigration - Bergmann, Simone; Rohde, Manfred; Preissner, Klaus T.; Hammerschmidt, Sven (Thrombosis and Haemostasis, 2005)
The glycolytic enzyme α-enolase represnts one of the nonclassical cell surface plasminogen-binding proteins of Streptococcus pneumoniae. In this study we investigated the impact of an internal plasminogen-binding motif of enolase on degradation of extracellular matrix and pneumococcal transmigration. In the presence of host-derived plasminogen activators (PA) tissuetype PA or urokinase PA and plasminogen S. pneumoniae expressing wild-type enolase efficiently degraded Matrigel or extracellular matrix (ECM). In contrast, amino acid substitutions in the nine residue plasminogen-binding motif of enolase significantly reduced degradation of ECM or Matrigel by mutated pneumococci. Similarly, recombinant wild-type enolase but not a mutated enolase derivative that lacks plasminogen-binding activity efficiently degraded ECM and Matrigel, respectively. In particular, bacterial cell enolase-bound plasmin potentiated dissolution of fibrin or laminin and transmigration of pneumococci through a fibrin matrix. In conclusion, these results provide evidence that the enolase is the major plasminogen-binding protein of pneumococci and that the nine residue plasminogen-binding motif of enolase is the key cofactor for plasmin-mediated pneumococcal degradation and transmigration through host ECM.
Keywords: Pneumococci; plasmin activity; enolase; fibrinolysis; degradation